Assessment of suicide probability and related factors in male incarcerated adolescents; a sample of reformatory center in Turkey. (September 2021) - Karatoprak, Serdar; Ayaz, Nusret; Dönmez, Yunus Emre; Dogan, Mustafa
Abstract: Objective: Suicidal behavior in adolescents is an important public health problem, and it ranks first among the causes of prison deaths in incarcerated adolescents(IAs). The aim of this study is to determine the probability of suicide and associated risk factors in IAs. Method: Seventy-one male adolescents in a reformatory center were contrasted with a matched group of 71 male adolescent with no psychiatric disorder and no criminal record. Suicidal probability and psychiatric symptomatology were assessed with the Suicide Probability Scale, SA-45 Questionnaire, respectively. Results: It was determined that the probability of suicide was higher in IAs, and depression and hostility symptoms, the presence of another individual involved in delinquency in family had predictive effects. It was also found that there was a positive correlation between the probability of suicide and the number of delinquencies, the number of incarceration, and a negative correlation between attending to school or work while in reformatory and being visited by relatives while in reformatory. Conclusions: The results suggest that when assessing suicide risk for IAS, it may be useful to pay attention to those with symptoms of depression or hostility, those with multiple delinquencies or entrance to reformatory, and those who have family members involved in delinquency.